2019
DOI: 10.1101/862581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic Brain Tumor Delivery of Synthetic Protein Nanoparticles for Glioblastoma Therapy

Abstract: Glioblastoma multiforme (GBM), the most aggressive form of brain cancer, has witnessed very little clinical progress over the last decades, in parts, due to the absence of effective drug delivery strategies. Intravenous injection is the least invasive delivery route to the brain, but has been severely limited by the blood-brain barrier (BBB). Inspired by the capacity of natural proteins and viral particulates to cross the BBB, we engineered a synthetic protein nanoparticle (SPNP) based on polymerized human ser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 60 publications
0
32
0
1
Order By: Relevance
“…SPNPs were synthesized using a modification of the well-established EHD co-jetting technique [ 51 53 ]. Generally, SPNPs are generated by dissolving a protein of interest and a copolymer of choice into a co-solvent system of water and an organic solvent, such as ethanol or ethylene glycol [ 16 ]. The mixture is then ejected through a small-gauge needle towards a collecting surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPNPs were synthesized using a modification of the well-established EHD co-jetting technique [ 51 53 ]. Generally, SPNPs are generated by dissolving a protein of interest and a copolymer of choice into a co-solvent system of water and an organic solvent, such as ethanol or ethylene glycol [ 16 ]. The mixture is then ejected through a small-gauge needle towards a collecting surface.…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, we have adapted electrohydrodynamic (EHD) co-jetting techniques, previously established by the Lahann lab, to create single-compartment and anisotropic (i.e., multicompartmental) synthetic protein nanoparticles (SPNPs and ASPNPs, respectively), which can be easily made from a variety of proteins [ 13 15 ]. A recent publication demonstrated how this versatile technique can be used to create particles with a significant therapeutic potential, in particular to treat glioblastoma [ 16 ]. To translate the promising benefits of these particles into the clinic, specific characterization techniques for anisotropic particles need to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…A small library of commercially available macromers was selected to investigate different sol/gel transitions. The first two macromers, 2 KDa O,O′-bis[2-(N-succinimidylsuccinylamino)ethyl]polyethylene glycol (PEG-NHS) and 4,7,10,13,16,19,22,25,32,35,38,41,44,47,50,53-hexadecaoxa-28,29-dithiahexapentacontanedioic acid di-N-succinimidyl ester (PEG-NHS-S), react the macromers' ester functional groups with the proteins' amine groups. This reaction completes after SPNPs are deposited by EHD jetting onto the collecting surface and then placed at 37 °C for 7 days.…”
Section: Protein Nanoparticles Are a Promising Approach For Nanotheramentioning
confidence: 99%
“…We have recently demonstrated that local treatment of glioma with sHDL-mimicking nanodiscs By the modification of the NPs with various coating materials, efficient delivery of molecules can be achieved [258,259]. One such modification, tumor-penetrating peptide, iRGD has been shown to facilitate the NP transport and CNS penetration [260][261][262]. We recently demonstrated that albumin NPs loaded with siRNA against signal and transducer of activation 3 (STAT3) transcription factor (which inhibits immune functions upon activation), and iRGD penetrate the BBB and that, when administered in combination with SOC, extend MS of mice bearing glioma and elicit robust antiglioma immune response [262].…”
Section: Nanotechnologiesmentioning
confidence: 99%
“…For example, nanoparticles injected i.v. composed of albumin, a siRNA against STAT3 and the tumor penetrating peptide iRGD, showed effective brain tumor delivery and a significant survival benefit in an aggressive glioma model [262]. It would be interesting to test the efficacy of these particles for the delivery of immune-stimulatory agents in the clinical setting.…”
Section: Expert Opinionmentioning
confidence: 99%